Diversity of Food Source and Foraging Behavior of Tetragonula laeviceps (Hymenoptera: Meliponini) in Parigi Selatan Sub District - Nuraini, Nuraini; Trianto, Manap; Alimudin, Sukmawati (BIO-EDU: Jurnal Pendidikan Biologi, 2020)
Tetragonula laeviceps is a type of stingless bee that is currently widely cultivated in Indonesia due to ability to produce various products that have many uses for human life. Foraging behavior is the main activity of honey bee to fulfill their daily needs. The availability of food source is one of the important factor that influence the foraging behavior of Tetragonula laeviceps. This study aims to determine the diversity of food source and foraging behavior of Tetragonula laeviceps. Observing the diversity of food source through identification of pollen and observing the foraging behavior of the bee. The diversity of pollen found in Parigi Selatan Regency showed that there were 20 families of food sources of Tetragonula laeviceps and the most frequently visited family is Arecaceae. Foraging behavior of Tetragonula laeviceps begins at sunrise until evening. The peak of activity occurs in the morning around 08.30-08.40 WITA and the afternoon around 15.30-15.40 WITA which is related to the availability of food source. Environmental factors (air temperature, humidity, and light intensity) affect the foraging behavior of Tetragonula laeviceps.